Tunable graphene-based polarizer - Bludov, Yuliy V. (2012)
It is shown that an attenuated total reflection structure containing a graphene layer can operate as a tunable polarizer of the electromagnetic radiation. The polarization of the reflected electromagnetic wave is controlled by adjusting the voltage applied to graphene via external gate, as demonstrated for the cases of linearly and circularly polarized incident radiation. The mechanism is based on the resonant coupling of p-polarized waves to the surface plasmon-polaritons in graphene. The presented calculations show that, at resonance, the reflected wave is almost 100% s-polarized.